2014
DOI: 10.1371/journal.pone.0109653
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Program Expansion in Zambézia Province, Mozambique: Geospatial Mapping of Community-Based and Health Facility Data for Integrated Health Planning

Abstract: ObjectiveTo generate maps reflecting the intersection of community-based Voluntary Counseling and Testing (VCT) delivery points with facility-based HIV program demographic information collected at the district level in three districts (Ile, Maganja da Costa and Chinde) of Zambézia Province, Mozambique; in order to guide planning decisions about antiretroviral therapy (ART) program expansion.MethodsProgram information was harvested from two separate open source databases maintained for community-based VCT and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Of note, while this review was focused on more technologically and methodologically sophisticated applications, several articles not included in this review demonstrated the utility of simply visually displaying mapped data points, such as for plotting the locations of HIV services [83] and risky sexual behaviors [8488]. Mapping the overlap of service provision and demand was useful for selecting priority areas for programmatic expansion [81, 89, 90]. Program implementation could benefit from dynamic, interactive and iteratively updated maps with verified health facility coordinates and infrastructure data [91] and simple mapping may be good entry point for more advanced geospatial techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, while this review was focused on more technologically and methodologically sophisticated applications, several articles not included in this review demonstrated the utility of simply visually displaying mapped data points, such as for plotting the locations of HIV services [83] and risky sexual behaviors [8488]. Mapping the overlap of service provision and demand was useful for selecting priority areas for programmatic expansion [81, 89, 90]. Program implementation could benefit from dynamic, interactive and iteratively updated maps with verified health facility coordinates and infrastructure data [91] and simple mapping may be good entry point for more advanced geospatial techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Much of Zambézia Province´s rural districts, such as Maganja da Costa, have populations dispersed over large geographic regions and consists of subsistence farmers or fisherman, with limited educational opportunities, and who rely on health infrastructure which was heavily damaged or destroyed during Mozambique´s 16-year civil war (1976–1992) [ 8 , 15 ]. In addition, severe health worker shortages, high staff turnover, and fragile health systems further compound the challenges that patients encounter when accessing care in these rural districts [ 10 , 45 , 46 ]. Since the inception of Mozambique´s HIV program, distance needed to travel to a health facility has been thought to be one of the major barriers to accessing care and patient retention.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of Geographic Information System (GIS) and spatial analysis in enhancing the effectiveness of health providers and monitoring immunization coverage has been emphasized in other Central African countries [15][16][17][18]. Other illustrations of the application of geospatial mapping to address health issues such as malnutrition and guiding program planning in resource-limited settings, or reducing measles incidence through frequent supplementary immunization activities were also found in the literature [19,20].…”
Section: Discussionmentioning
confidence: 99%